Exercise training and burdock root (Arctium lappa L.) extract independently improve abdominal obesity and sex hormones in elderly women with metabolic syndrome - Ha, Min-Seong (Sci Rep, 2021)
The prevalence of metabolic syndrome (MS) is increasing among the elderly, and new lifestyle-based treatment strategies are warranted. We conducted a randomized, double-blind controlled trial of the effects of aquatic exercise (AE) and/or consumption of burdock root extract (BE) on body composition and serum sex hormones, i.e., testosterone, estradiol, sex hormone-binding globulin (SHBG), and dehydroepiandrosterone-sulfate (DHEA-S) in elderly women with MS. The percentage of abdominal fat was decreased in the AE group. Waist circumference was increased in the control (CON) group, but not in the other groups. SHBG and estradiol levels were enhanced by both AE and BE and correlated with changes in fat-related body composition. DHEA-S levels only increased in the BE group, which was consistent with changes in lean body mass. Testosterone levels decreased in the CON group, which correlated with changes in lean body mass, skeletal muscle mass, body fat, and waist circumference. Our findings suggested that the combined AE/BE intervention exerted no synergistic and/or additive effects on any sex-related outcome measures in elderly women with MS.